2x-4y=2 -2x+3y=0 elimination

Answers

Answer 1
Answer: 2x-4y=2 \n\underline{-2x+3y=0} \n-4y+3y=2+0 \n-y=2 \ny=-2 \n \n2x-4y=2 \n2x-4 * (-2)=2 \n2x+8=2 \n2x=2-8 \n2x=-6 \nx=(-6)/(2) \nx=-3 \n \n(x,y)=(-3,-2)
Answer 2
Answer:

2x-4y=2

-2x+3y=0

-------------------- (+)

3y-4y=2

-y=2   /*(-1)

y=-2

2x-4y=2

2x-4*(-2)=2

2x+8=2   /-8

2x=-6

x=-3



Related Questions

How many significant figures are in the measurement 0.0105 km?a. 2 b. 3 c. 4 d. 5
The diagram shows a solid which is half of a cone. Calculate the total surface area of the solid. a. ( 48 + 48 ) b. ( 48 + 15 ) c. ( 48 + 30 ) d. ( 24 + 15 )
How do I find this answer 20=4x
Describe how the equation y equal left parenthesis x minus 2 right parenthesis to the power of 2 plus 5 transforms the graph of a basic parabola y equal x to the power of 2 .
Factor the expression y2+6y-16

Find the product.(7x - 6)2
A. 49x2 + 36
B. 49x2 - 84x + 36
C. 7x2 - 84x + 36
D. 7x2 + 36

Answers

When we square brackets, it is always advised to write out the brackets fully.
(7x - 6)² becomes
(7x - 6)(7x - 6)

Next, we follow FOIL
First (The first term in the set 1 multiplied by the first term in set 2)
Outer (The first term in set 1 multiplied by the second term in set 2)
Inner (The second term in set 1 multiplied by the first term in set 2)
Last (The second term in set 1 multiplied by the second term in set 2)

F   7x  x  7x = 49x²
O  7x  x  -6  = -42x
I    -6  x  7x  = -42x
L
  -6  x  -6  = 36

Now, we add together all the terms

49x² + -42x + -42x +36

Adding a negative is the same as subtracting

49x² - 42x - 42x + 36

Finally, simplify (add together the like terms)

49x² -84x + 36

Answer:

Option B: 49x² -84x + 36

Step-by-step explanation:

5. Find the percent change: Original 91, New 77*​

Answers

The percent change is 14
The percent change is 14.

Solve the triangle.a equals 60 b equals 22 c equals 50
whoever answers right in the next five minutes get the brainiest thing

Answers

∠A = 106.3°, ∠B = 20.6°, ∠C = 53.1°

Step-by-step explanation:

In a ΔABC, the sides opposite to the angle A is a, angle B is b, and angle C is c. a = 60 , b= 22, c = 50

We can find any one angle by cosine rule,

a² = b² + c² - 2 bc cos (A)

60² = 22² + 50² - 2(22)(50) cos A

3600 = 484 + 2500 - 2200 cos A

3600 = 2984 - 2200 cos A

3600 - 2984 = -2200 cos A

616 = -2200 cos A

cos A = 616/ -2200 = -0.28

A = cos⁻¹ (-0.28) = 106.3°

Now we can use sine rule to find angle B as,

sin A/ a = sin B / b

sin  106.3° / 60 = sin B / 22

sin B = 22 × sin  106.3° / 60

 B = sin⁻¹ (22 × sin  106.3° / 60 ) = 20.6°

As we know the sum of angles in a triangle is 180°.

∠A + ∠B + ∠C = 180°

106.3° + 20.6° + ∠C = 180°

126.9° + ∠C = 180°

∠C = 180° - 126.9° = 53.1°

Express the area A of a rectangle as a function of the length x if the length of the rectangle is twice its width.

Answers

A = L  x  W
L = x
L = 2 W
W = L/2 = x/2
A = x * x / 2
A = x² / 2
Answer:
The area of a rectangle is x²/2.
The function is 2/3 and 4/28

How do I show the distributive property for 6x7

Answers

6*7

=6(1+1+1+1+1+1+1)

=6*1+6*1+6*1+6*1+6*1+6*1+6*1

=6+6+6+6+6+6+6

=42


the answer is 42 because there is no other numbers in parentheses

 

Whats the formula of an rectangle

Answers

Answer:

Perimeter: 2l+2w

Area: lw

Step-by-step explanation:

Let l=length, and w=width

Answer:

For Perimeter its  2times length + 2times width

and for Area its: length times width

Hope this helps :)